“HE RETURNED MEMORY TO UKRAINIANS”: ARTISTIC-PHILOSOPHICAL COMPREHENSION OF SHEVCHENKO AS THE NATION’S CODE IN TARAS TABACHYN’S WORK “NA ROZPUTTIAKH VELELIUDNYKH” - Shevchuk, L. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the research of Shevchenko’s word as the unique code in T. Tabachyn’s poetic work, to the revelation of its problematic-stylistic peculiarity.